THE INFLUENCE OF THE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) MODEL ON THE APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGY AT ELEMENTARY SCHOOLS - Silvia Kartika Ningsih; Akhmad Habibi; Muhammad Sofwan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper examines the effect of applying Information and Communication Technology (TIK) in the learning process through the UTAUT model. There are four components seen from the UTAUT model, namely Performance Improvement Expectations, Business Improvement Expectations, Social Influence, and Supporting Conditions. The population used in the research were teachers at three schools in Jambi, namely SDN 47/IV, SDN 66/IV, and SDIT Al Azhar. The sample in the research involved 130 teachers in the three schools. The research is quantitative research. Research data were obtained through survey methods and questionnaires. The data analysis used in the research is PLS-SEM. The results indicate that the four components of the UTAUT model had a significant influence on the use of Information and Communication Technology (TIK) applied by teachers in the learning process. The most influential component of UTAUT through Information and Communication Technology applied by teachers is the Supporting Conditions. Based on the results of the research, it can be concluded that the unified theory of acceptance and use of technology model has an influence on the use of Information and Communication Technology (TIK) applied by elementary school teachers in the learning process.